Teen innovators : nine young people engineering a better world with creative inventions - Estes, Fred, 1950- (Zest Books, 2022)
Profiles nine young people who have created inventions that have improved others' lives, and chronicles how they came up with and built their ideas--including Jack Andraka's test to better detect cancer, William Kwamba and his electricity-producing windmill, and a group of teens who built a champion robot. Includes illustrations, photographs, and a glossary.